Isolated Pulmonary Arterial Thrombosis in Patient with Eisenmenger Syndrome Treated with Catheter-directed Thrombolysis: A Case Report and Literature Review - Dya Pratama Andryan; Vienna Rossimarina; Daniel Paringotan L. Tobing; Taofan Taofan; Bambang Widyantoro (Acta Medica Indonesiana)
The concept of venous thromboembolism (VTE) has recently been revisited because of evidence of a new spectrum of the disease called in situ pulmonary arterial thrombosis (ISPAT). We present the case of a 40-year-old female with shortness of breath, who was referred from a regional hospital because of a secundum atrial septal defect. Using echocardiography and computed tomography pulmonary angiogram, she was diagnosed with ISPAT. She received catheter-directed thrombolysis with good results. Knowing the difference in diagnostic clues between classical VTE and ISPAT is crucial, especially for managing the patient correctly.